Unusual rearrangement of dihalocyclopropanes. Issue 4 (2003) - Jankowski Jankowski, Christopher K. Christopher K.; Laouz Laouz, Antoun Bou Antoun Bou; Lesage Lesage, Denis Denis; Diaz T. Diaz T., Eduardo Eduardo
Abstract : Dihalocyclopropanation of the double bond of some olefins, leading to dihalocyclopropanes, offered an opportunity to perform their rearrangement to dihalomethylvinyl with Hiyama type reagents, in presence of cationic system such as Cr 2+ /Cr 3+ . The chain elongation of alkenes via the gem‒dihalocyclopropanes produced α, β –unsaturated aldehydes and acids.